Morphological and molecular characterization, pathogenicity and sexual reproduction of Ascochyta rabiei isolates of chickpea fields in Argentina - Crociara, Clara Sonia; Valetti, Lucio; Bernanrdi Lima, Nelson; Iglesias, Juliana; Pastor, Silvina (Wiley, 2022)
Ascochyta blight is one of the most devastating foliar diseases of chickpea. The causal agent, Ascochyta rabiei, is a heterothallic ascomycete and its sexual reproduction depends on the proximate presence of both mating types, MAT1-1 and MAT1-2. Since its first detection in Argentina in 2011, very few studies have been carried out and information on local isolates remains unknown. In this work, 12 isolates were obtained from the northern, central and southern regions of Córdoba province, Argentina. First, isolates were tentatively identified as A. rabiei based on their colony and conidial characteristics. Identity was confirmed by phylogenetic analysis of the ITS, β-tubulin and D1/D2 loci. Morphology, cultural characteristics and pathogenic variability of the isolates were compared. Likewise, 27 crosses were made to demonstrate possible sexual reproduction between the strains. The isolates showed differences in morphology (shape, texture, conidial size, colony colour, growth rate) and aggressiveness from a susceptible cultivar. All crosses were fertile and produced pseudothecia, asci and ascospores. This work is the first in Latin America to characterize isolates of A. rabiei morphologically and molecularly, examine their pathogenic variability and demonstrate the sexual reproduction between isolates carrying different mating-type idiomorphs. New levels of aggressiveness in A. rabiei or adaptive changes like resistance to fungicides or breakdown of host resistance are a distinct possibility in the future.